Inhibition of hyphae formation and SIR2 expression in Candida albicans treated with fresh Allium sativum (garlic) extract - Low, Chen Fei; Chong, Pei Pei; Yong, Phelim Voon Chen; Lim, Crystale Siew Ying; Ahmad, Zuraini; Othman, Fauziah (The Society for Applied Microbiology, 2008)
Aims: The aims of the present study were to determine whether Allium sativum (garlic) extract has any effect on the morphology transformation of Candida albicans, and to investigate whether it could alter the gene expression level of SIR2, a morphogenetic control gene and SAP4, a gene encoding secreted aspartyl proteinase.